Avaliação da resistência à compressão de um solo compactado em diferentes umidades e submetido à variação do grau de saturação - Lima, Cicero Renato (Universidade Federal Rural do Semi-Árido, 2019)
The dictionary is about the characteristics of soils of great importance for an engineering when it comes to mass movement. One should be aware of what the massive with the external forces that serve as raw material if the most different ways of subordinating themselves to the situation. Thus, the present work aims to study and verify the behavior of a characteristic soil of the municipality of Pau dos Ferros / RN when compacted in the different humidities and submitted to a variation in its degree of saturation, the situation is common in engineering works . The methodological path was from a collection of the soil mass to the preparation of the specimens. The compaction provided a compaction curve that showed an excellent condition and an analysis of new specimens in the distinct branches of the same curve. The study was proven with a saturation of compact soils with a great influence in the treatment of its resistance to compression. The resistance variation for the dry branch was relevant, reaching 70% in the force gain when the degree of saturation after the compression decreased, whereas, in the larger dose, this gain was only 4%. Already the resistance losses reached 60% last night in an increase in their degree of saturation, whereas in the dry branch the body was found only in 17%. and saturated post-compactation, but at more than a night out from the saturation saturation post saturation.
Keywords: Estabilidade; Umidade Ótima; Compressão Simples; Stability; Optimal Humidity; Simple Compression; ENGENHARIAS::ENGENHARIA CIVIL